Testosterone replacement therapy and cardiovascular events - Alp Burak Çatakoğlu; Muammer Kendirci (KARE Publishing, 2017)
A low testosterone level and hypogonadism are associated with cardiovascular disease. Aging, chronic health problems, and obesity are all associated with a low testosterone level as well as the presence and severity of cardiovascular disease. Testosterone is increasingly prescribed for patients with clinical hypogonadism and a low testosterone level. The information we have is still contradictory regarding testosterone replacement therapy (TRT) and its association with adverse cardiovascular events. Older patients and patients who are susceptible to cardiovascular diseases could be at risk with a testosterone prescription. This is a review of the literature to discuss the cardiovascular safety of TRT.